MODELING OF HARDWARE AND ALGORITHMIC STRUCTURE OF MOBILE MULTIPOSITIONING RADIO RANGEFINDING NAVIGATION AND LANDING AEROSYSTEM IN ITS SPATIAL CONFIGURATION - Ya. V. Kondrashov; T. S. Fialkina; A. P. Ryabets (Научный вестник МГТУ ГА, 2016)
The concept of structuring of radio equipment, mathematical and algorithmic tools to provide computing operations for determining the location of aircraft in spatial configuration of mobile (portable) multipositioning radio rangefinding interrogation-reply navigation and landing system is considered in this article. The mathematical modeling of algorithms of aircraft traffic terminal control is carried out. The results of calculations of potential system performance and its analysis for compliance with international safety requirements are represented.